A monoclonal antibody to CD4 domain 2 blocks soluble CD4-induced conformational changes in the envelope glycoproteins of human immunodeficiency virus type 1 (HIV-1) and HIV-1 infection of CD4+ cells. - Moore, J P (1992)
The murine monoclonal antibody (MAb) 5A8, which is reactive with domain 2 of CD4, blocks human immunodeficiency virus type 1 (HIV-1) infection and syncytium formation of CD4+ cells (L. C. Burkly, D. Olson, R. Shapiro, G. Winkler, J. J. Rosa, D. W. Thomas, C. Williams, and P. Chisholm, J. Immunol., in press). Here we show that, in contrast to the CD4 domain 1 MAb 6H10, 5A8 and its Fab fragment do not block soluble CD4 (sCD4) binding to virions, whereas they do inhibit sCD4-induced exposure of cryptic epitopes on gp41 and dissociation of gp120 from virions. Two other MAbs, OKT4 and L120, which are reactive with domains 3 and 4 of CD4, have little or no effect on HIV-1 infection, syncytium formation, or sCD4-induced conformational changes in the envelope glycoproteins. The mechanisms of action of 5A8 and 6H10 can be further distinguished in syncytium inhibition assays: 6H10 blocks competitively, while 5A8 does not. We opine that 5A8 blocks HIV-1 infection and fusion by interfering with conformational changes in gp120/gp41 and/or CD4 that are necessary for virus-cell fusion.